Morphometric Characterization of Human Coronary Veins and Subvenous Epicardial Adipose Tissue—Implications for Cardiac Resynchronization Therapy Leads - Keiler, Jonas; Meinel, Felix G.; Ortak, Jasmin; Weber, Marc-André; Wree, Andreas; Streckenbach, Felix (Frontiers in Cardiovascular Medicine, 2020)
Subvenous epicardial fat tissue (SEAT), which acts as an electrical insulation, and the venous diameter (VD) both constitute histomorphological challenges for optimal application and lead design in cardiac synchronization therapy (CRT). In this study, we characterized the morphology of human coronary veins to improve the technical design of future CRT systems and to optimize the application of CRT leads. We retrospectively analyzed data from cardiac computed tomography (CT) of 53 patients and did studies of 14 human hearts using the postmortem freeze section technique and micro CT. Morphometric parameters (tributary distances, offspring angles, luminal VD, and SEAT thickness) were assessed. The left posterior ventricular vein (VVSP) had a mean proximal VD of 4.0 ± 1.4 mm, the left marginal vein (VMS) of 3.2 ± 1.5 mm and the anterior interventricular vein (VIA) of 3.9 ± 1.3 mm. More distally (5 cm), VDs decreased to 2.4 ± 0.6 mm, 2.3 ± 0.7 mm, and 2.4 ± 0.6 mm, respectively. In their proximal portions (15 mm), veins possessed mean SEAT thicknesses of 3.2 ± 2.4 (VVSP), 3.4 ± 2.4 mm (VMS), and 4.2 ± 2.8 mm (VIA), respectively. More distally (20–70 mm), mean SEAT thicknesses decreased to alternating low levels of 1.3 ± 1.1 mm (VVSP), 1.7 ± 1.1 mm (VMS), and 4.3 ± 2.6 mm (VIA), respectively. In contrast to the VD, SEAT thicknesses alternated along the further distal vein course and did not display a continuous decrease. Besides the CRT responsiveness of different areas of the LV myocardium, SEAT is a relevant electrophysiological factor in CRT, potentially interfering with sensing and pacing. A sufficient VD is crucial for successful CRT lead placement. Measurements revealed a trend toward greater SEAT thickness for the VIA compared to VVSP and VMS, suggesting a superior signal-to-noise-ratio in VVSP and VMS.